Cloning, transformation and expression of cell cycle-associated protein kinase OsWee1 in indica rice (Oryza sativa L.) - Frengky H.H. Prasetyo; Bambang Sugiharto; Netty Ermawati (Journal of Genetic Engineering and Biotechnology, 2018)
The development process of seed in plants is a cycle of cells which occur gradually and regularly. One of the genes involved in controling this stage is the Wee1 gene. Wee1 encode protein kinase which plays an important role in phosphorylation, inactivation of cyclin-dependent kinase 1 (CDK1)-cyclin (CYC) and inhibiting cell division at mitotic phase. The Overexpression of Wee1 leads to delaying entry into mitotic phase, resulting in enlargement of cell size due to suppression of cell division. Accordingly, the cloning and overexpressing of Wee1 in rice plant is important aim of this research in achieving better quantity and quality of future rice. The main objective of this present study is to cloning and generate transgenic rice plants overexpressing of Wee1 gene. Wee1 was isolated from cDNA of indica rice (Oryza sativa), called OsWee1. The full length of OsWee1 was 1239 bp in size and successfully inserted into plant expression vector pRI101ON. Seven-day-old rice seedlings were prepared for transformation of OsWee1 gene using Agrobacterium-mediated transformation method. Four positive transgenic lines were identified through the presence of kanamycin resistance gene (nptII) using genomic PCR analysis. Southern blot analysis result provides evidence that four independent rice transformants contained one to three rearranged transgene copies. Further screening in transgenic rice generation is needed in order to obtain stable expression of OsWee1. Keywords: Agrobacterium, Cell cycle, Gene transformation, OsWee1, Protein kinase, Transgenic rice